POST-STROKE VISUAL FIELD DEFECTS AND OTHER OPHTHALMOLOGICAL ABNORMALITIES: A RETROSPECTIVE STUDY - ROOPA ROKHADE,; PRADEEP KUMAR JAIN, (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The study aimed to estimate prevalence of visual field defects (VFDs) and other ophthalmological abnormalities in post-stroke patients. Methods: This retrospective study, conducted in department of ophthalmology in collaboration of department of neurology of a tertiary care medical institute, analyzed data from 80 adult patients undergoing ophthalmological examination including perimetry for presence of VFDs. Demographic data, including age and gender were extracted. Medical records were reviewed to assess visual disturbances, systemic illnesses, and medications. Gender distribution and presence of risk factors such as diabetes and hypertension were analyzed. Ophthalmological findings and the type and severity of VFDs were noted from perimetry reports. Magnetic resonance imaging and computed tomography scans were analyzed to identify brain lesions causing VFDs. Results: In a study of 80 stroke patients, males were more prevalent (58.8%) than females (41.2%), with the most affected age group being 31– 40 years (33.8%). Hypertension was the most common risk factor (35.0%), and ischemic stroke was the most frequent type (66.3%). The anterior circulation was the predominant site of lesions (85.0%). The most frequent VFDs was complete homonymous hemianopia, observed in 20 patients (25.0%), followed by partial homonymous hemianopia in 6 patients (7.5%). Constriction and inferior quadrantanopia were each noted in 3 patients (3.75%), while superior quadrantanopia was seen in 2 patients (2.5%). Hemianopia combined with quadrantanopia and scotoma were the least common (1.25% each). The other common ophthalmological finding was gaze palsy which was seen in 13 (16.25%) patients. Conclusion: Visual filed defects and other ophthalmological manifestations such as gaze palsies are common in post-stroke patients. Early detection and targeted rehabilitation of these abnormalities enhance recovery, reduce disability and optimize outcomes for stroke survivors.